COMPOSITION AND DISTRIBUTION OF DOLPHIN IN SAVU SEA NATIONAL MARINE PARK, EAST NUSA TENGGARA - Mujiyanto Mujiyanto; Riswanto Riswanto; Dharmadi Dharmadi; Wildan Ghiffary (Research Center for Fisheries, 2017)
Dolphins are one of the most interesting cetacean types included in family Delphinidae or known as the oceanic dolphins from genus Stenella sp. and Tursiops sp. Migration and abundance of dolphins are affected by the presence of food and oceanographic conditions. The purpose of this research is to determine the composition and distribution of dolphins in relation to the water quality parameters. Benefits of this research are expected to provide information on the relationship between distributions of the family Delphinidae cetacean (oceanic dolphins) and oceanographic conditions. The method for this research is descriptive exploratory, with models onboard tracking survey. Field observations were done in November 2015 and period of March-April 2016 outside and inside Savu Sea National Marine Park waters. The sighting of dolphin in November and March-April found as much seven species: bottlenose dolphin, fraser’s dolphin, pantropical spotted dolphin, risso’s dolphin, rough-toothed dolphin, spinner dolphin and stripped dolphin. The highest species distribution noted in the Savu Sea is spinner dolphin, pantropical spotted dolphin, rough-toothed dolphin and frazer’s dolphin. The existence of dolphins in Savu Sea is more related with sea surface temperature than others oceanographic parameters. This condition is suspected due to the influence of sea surface temperature to body temperature of dolphin especially for foraging activities. The habit of dolphin is more active around Sumba Island and Daratan Timor waters while in the evening the animal is usually going to Manggarai and Rote Ndao Islands waters to rest.